Рак щитоподібної залози фолікулярного походження: клініко-морфологічні характеристики та прогноз - Ларін, О. С.; Кротевич, М. В.; Хоперія, В. Г.; Галахін, К. О. (Clinical Endocrinology and Endocrine Surgery, 2017)
In this article the main histopathological features of differentiated follicular thyroid carcinoma, caracters influencing their prognosis were analysed. In all cases distant metastasis, extrathyroid invasion and age are the most significant features; histology, limitation and differentiation are then involved. The diagnosis of malignancy suspected on the fine needle aspiratuion cytology must be confirmed on the frozen sections at the time of surgery; in the main time extention and histological type can be determined and help to choose the treatment.